Proliferative potential in benign mixed salivary gland tumors, using Ki67 marker in relation to different clinicopathological parameters - Muhammad, Layla M.; Mousa, Chenar M.; Abdulqadir, Henan A. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Pleomorphic adenoma is the most common benign tumor of the salivary gland. It shows a remarkable degree of morphological diversity. Immunohistochemical Ki67 expression is used to predict the proliferative potential of the growth. The aim of this study was to evaluate the expression of the proliferation marker Ki-67 in benign mixed salivary gland tumors.Methods: Fifty five paraffin embedded tissue blocks were included in the study. After histopathological reassessment of hematoxylin and eosin stained section for each block, an immunohistochemical staining was performed using anti-Ki67 protein.Results: From total number of 55 cases, 58.1% of patients were in group aged ≤ 40 years. The male to female ratio was 1.037:1. The parotid gland was the most affected (56.37%) gland. The mean duration of lesions before treatment was 17.96 months and the mean size of tumors was 3.76 cm. Histologically, cell-rich subtype constituted 54.54%, followed by stroma-rich (34.55%), and only 10.91% of cases were classic. Ki67 expression was positive in 18.18% predominantly in epithelial variant with a weak score in nine cases (16.36%). Six of positive cases were in parotid gland and two cases in the submandibular gland. Only one case was in minor salivary gland. Moderate Ki67 expression score was seen in one epithelial variant case (14.28 %) associated with parotid gland.Conclusion: Immunohistochemical expression of Ki-67 in pleomorphic adenoma was characterized by low proliferative rate and predominantly seen in epithelial tumor variants.